Cell Recoverability and Metabolism of Colwellia Psychrerythraea During Yearlong Incubations At Ultra-Cold Temperatures, 2020-2021 ... - Firth, Evan; Junge, Karen (NSF Arctic Data Center, 2024)
Liquid water is essential to life as we know it, yet most planets and moons in our solar system have surface temperatures well below the freezing point of pure water. As part of an effort to identify potential biosignatures and biosignature targets for upcoming space-exploration life detection missions, arctic strain Colwellia psychrerythraea 34H was incubated at a range of ultra-cold temperatures over the course of a year-long study. Samples were examined for cell abundance, recoverability, and metabolic activity over the course of the incubation period at -36, -70, and -196 degrees Celsius (°C). This is the compiled raw data from these experiments. This research was undertaken at the Applied Physics Laboratory at the University of Washington, Seattle between 2020 and 2021. ...